Acute myeloid leukaemia with t(8;21) associated with "occult" mastocytosis. Report of an unusual case and review of the literature. Issue 3 (27th February 2004) - Bernd, H-W; Sotlar, K; Lorenzen, J; Osieka, R; Fabry, U; Valent, P; Horny, H-P
Abstract : Approximately 20% of patients with systemic mastocytosis (SM) have an associated haematological, clonal, non-mast cell lineage disease, and most exhibit an associated myelogenous neoplasm. This report describes a 48 year old man with acute myeloid leukaemia (AML) and a type t(8;21) cytogenetic abnormality. Associated bone marrow mastocytosis (a defined subtype of SM) was only detected after successful polychemotherapy in the state of bone marrow aplasia, and persisted after complete remission of AML. The diagnosis of mastocytosis was based on the demonstration of a multifocal dense mastocytic infiltrate. The atypical mast cells showed prominent spindling and an aberrant immunophenotype, with coexpression of tryptase, chymase, KIT, and CD25—which is expressed only on neoplastic (not normal) mast cells. In addition, the transforming somatic mutation D816V of the c-kit gene was detected. Re-examination of the pretherapeutic (initial) bone marrow revealed a slight diffuse increase in partially spindle shaped mast cells also exhibiting an abnormal immunophenotype, with CD25 expression, although compact mastocytic infiltrates were not detected. Because the D816V mutation was detected in the initial bone marrow specimen, strict application of three minor diagnostic criteria (spindling, CD25, D816V) enabled a diagnosis of SM-AML to be confirmed retrospectively in the initial bone marrow tissue.